Rate of conversion from mild cognitive impairment to dementia in a Thai hospital‐based population: A retrospective cohort - Papan Thaipisuttikul; Kriengsak Jaikla; Sirikorn Satthong; Pattarabhorn Wisajun (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction Mild cognitive impairment (MCI) is the state between normal cognition and dementia. This study objective was to estimate an average 1‐year rate of conversion from MCI to dementia and explore the associated factors of conversion in a hospital‐based cohort. Methods A retrospective cohort study of participants with MCI was conducted in a tertiary care hospital in Thailand. Two hundred fifty participants, 50 years of age or older, were enrolled. Results An average 1‐year conversion rate from MCI to dementia was 18.4%. MCI patients who converted to dementia were likely older (P < .001), predominantly female (P = .028), vitamin D deficient (P = .012), and associated with lower Mini–Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) scores during first assessments (P < .001, P < .001 respectively) and follow‐up assessments (P < .045, P < .001 respectively). We conducted two models of multivariate analysis, using binary logistic regression. In the first model, adjusted for age, sex, education, vitamin D deficiency, and first assessment MMSE scores, we found that underlying vitamin D deficiency (odds ratio [OR] = 3.13, 95% confidence interval [CI] 1.04 to 9.44) and first assessment MMSE scores (OR = 0.83, 95% CI 0.73 to 0.93) were significantly associated with conversion to dementia. In the second model, adjusted for age, sex, education, vitamin D deficiency and first assessment MoCA scores, only first assessment MoCA scores (OR = 0.58, 95% CI 0.45 to 0.76) were significantly associated with conversion to dementia. Discussion The 1‐year conversion rate from MCI to dementia was 18.4%. MMSE and MoCA were useful tools to assess baseline cognitive status in MCI patients and predict dementia progression. The association between vitamin D deficiency and risk of conversion from MCI to dementia requires further investigations.